On Existence and Uniqueness of Solutions of a Nonlinear Integral Equation - M. Eshaghi Gordji; H. Baghani; O. Baghani (Journal of Applied Mathematics)
The purpose of this paper is to study the existence of fixed point for a nonlinear integral operator in the framework of Banach space 𝑋∶=𝐶([𝑎,𝑏],ℝ𝑛). Later on, we give some examples of applications of this type of results.